A luminogenic lanthanide-based probe for the highly selective detection of nanomolar sulfide levels in aqueous samples12. Issue 36 (31st March 2017) - Aulsebrook, Margaret L.; Biswas, Suvendu; Leaver, Franklin M.; Grace, Michael R.; Graham, Bim; Barrios, Amy M.; Tuck, Kellie L.
Abstract : A novel bimetallic terbium(iii )/copper(ii ) complex for the luminescent detection of hydrogen sulfide in aqueous samples is described. Abstract : A bimetallic terbium(iii )/copper(ii ) complex (Tb-1·Cu 2+ ) for the time-gated luminescent detection of hydrogen sulfide in aqueous samples is reported. The probe shows excellent selectivity towards HS − over various anions and cations, including the ions common to natural waterways and waste water samples, displaying a 73-fold increase in luminescence in the presence of sulfide. The probe exhibits extremely fast reaction times and a low limit of detection (130 nM). The probe was used to quantify sulfide in an industrial "sour water" sample, with the result in excellent agreement with those from two independent assay methods (methylene blue and AzMC).